Aerobic Exercise and Fatigue in Rheumatoid Arthritis Participants: A Meta‐Analysis Using the Minimal Important Difference Approach. Issue 12 (28th November 2018) - Kelley, George A.; Kelley, Kristi S.; Callahan, Leigh F.
Abstract : Objective: To use the minimal important difference (MID) versus the standardized mean difference (SMD) approach in order to provide more robust and clinically relevant information regarding the association between land‐based aerobic exercise and changes in self‐reported fatigue among adults with rheumatoid arthritis (RA). Methods: Data from a previous meta‐analysis of 5 randomized controlled trials that represented up to 298 participants per study were utilized to calculate 9 effect sizes, using the MID approach. Data used to obtain the MID were derived from previously reported anchor‐based values specific to each fatigue instrument in adults with RA. Results were pooled using a random‐effects model. Results: Aerobic exercise resulted in statistically significant reductions in self‐reported fatigue (MID effect size −0.34 [95% confidence interval (95% CI) −0.58, −0.10]; P = 0.006). Results were similar when effect sizes were collapsed so that only 1 effect size represented each study (MID effect size −0.39 [95% CI −0.76, −0.03]; P = 0.04). Conclusion: Land‐based aerobic exercise is associated with statistically significant reductions in fatigue; however, based on previous cut points, it may be unlikely that a substantial number of participants with RA could obtain clinically relevant reductions in fatigue. Additional studies are needed, especially in those individuals with RA who have elevated levels of fatigue.